dental extractions, difficulty, close method or open method extractions. - I Gusti Ayu Raiyanti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Procrastination is a failure in doing the task within the desired time from or  put off task until the last moment. Academic procrastination is a kind delays that made the kind of formaltask related to academic task. The academic task such as writing assigments reading, stuying for exams, attending meeting (lectures), administrative task, and overall academic perfomance. Students who do most of procrastination in writing assigments by 46%. Moreover, the task of reading 30.1%, 27,6% studying for exams; attend meeting (lectures) 23% in 10.6% of administrative task, and overall academic perfomance of 10.2%. Characteristic of students  who perform procrastination is procrastination task until collection time limits (deadline), like not keeping promises to intermediatly collect duties  by giving reason to obtain additional time and choose to the order more enjoyable activities such as watching television, road-roads, an so on academic  Procrastination is affected by several factors. Procrastination done because students have the ability to evaluate anxiety, fear of failure, and difficulty making  decisions. Procrastination is also done because it requires the help of someone else to do this job, lazy, difficult  to set the time, and did not like his job.